Missense mutations in Desmocollin-2 N-terminus, associated with arrhythmogenic right ventricular cardiomyopathy, affect intracellular localization of desmocollin-2 in vitro - Basso Cristina; Occhi Gianluca; Bauce Barbara; Sigalotti Luca; Mancuso Luisa; Zaccolo Manuela; Lorenzon Alessandra; Salamon Michela; Nava Andrea; De Bortoli Marzia; Beffagna Giorgia; Lanfranchi Gerolamo; et al. (BMC, 2007)
Abstract Background Mutations in genes encoding desmosomal proteins have been reported to cause arrhythmogenic right ventricular cardiomyopathy (ARVC), an autosomal dominant disease characterised by progressive myocardial atrophy with fibro-fatty replacement. We screened 54 ARVC probands for mutations in desmocollin-2 (DSC2), the only desmocollin isoform expressed in cardiac tissue. Methods Mutation screening was performed by denaturing high-performance liquid chromatography and direct sequencing. To evaluate the pathogenic potentials of the DSC2 mutations detected in patients affected with ARVC, full-length wild-type and mutated cDNAs were cloned in eukaryotic expression vectors to obtain a fusion protein with green fluorescence protein (GFP); constructs were transfected in neonatal rat cardiomyocytes and in HL-1 cells. Results We identified two heterozygous mutations (c.304G>A (p.E102K) and c.1034T>C (p.I345T)) in two probands and in four family members. The two mutations p.E102K and p.I345T map to the N-terminal region, relevant to adhesive interactions. In vitro functional studies demonstrated that, unlike wild-type DSC2, the two N-terminal mutants are predominantly localised in the cytoplasm. Conclusion The two missense mutations in the N-terminal domain affect the normal localisation of DSC2, thus suggesting the potential pathogenic effect of the reported mutations. Identification of additional DSC2 mutations associated with ARVC may result in increased diagnostic accuracy with implications for genetic counseling.